2020
DOI: 10.1186/s12877-020-1490-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-frailty factors in community-dwelling 40–75 year olds: opportunities for successful ageing

Abstract: Background: There is little known about pre-frailty attributes or when changes which contribute to frailty might be detectable and amenable to change. This study explores pre-frailty and frailty in independent community-dwelling adults aged 40-75 years. Methods: Participants were recruited through local council networks, a national bank and one university in Adelaide, Australia. Fried frailty phenotype scores were calculated from measures of unintentional weight loss, exhaustion, low physical activity levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 49 publications
1
39
1
Order By: Relevance
“…It is worth mentioning that although the physical tests used in this study are simple, they assess habitual daily functions, which in turn are indicative of many underlying physiological processes ( Jones et al, 1999 ; Ferguson-Stegall et al, 2017 ). The improvements observed in cardiorespiratory fitness, resistance of the lower limb muscle strength, functional mobility, and gait speed in dual-tasks contribute to the functional independence of older adults and are associated with quality of life ( Gordon et al, 2020 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that although the physical tests used in this study are simple, they assess habitual daily functions, which in turn are indicative of many underlying physiological processes ( Jones et al, 1999 ; Ferguson-Stegall et al, 2017 ). The improvements observed in cardiorespiratory fitness, resistance of the lower limb muscle strength, functional mobility, and gait speed in dual-tasks contribute to the functional independence of older adults and are associated with quality of life ( Gordon et al, 2020 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prefrailty status fulfilling only one or two criteria of frailty also increased the risk of frailty [ 11 ]. One study showed some factors including high psychological distress, living alone, having health worries, and poor sleep quality; stair climbing, appetite, hydration; continence, and total food intake might be the predictive capacities for prefrailty to frailty [ 39 ]. With increasing age, there is also a decline in physical activity associated with decreases in exercise tolerance, which would lead to an increasing risk of frailty [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the replacement of these performance-based measures by self-report questions may be helpful in the development of an easy to apply frailty-screening tool, which may enable to screen large populations [6,10]. Although the two performance-based criteria (slowness and weakness) of the Frailty Phenotype were already replaced by questions in a few earlier studies (e.g., Santos-Eggimann and colleagues 2009, Gordon and colleagues 2020) [13,14], still little is known about which questions (or set of questions) are most valid to substitute the performance-based measures [10]. In most of the studies in which self-report questions were used, the validity of these questions was not tested, or at least not reported, while these modifications may have an important impact on its classification and predictive ability [10,15].…”
Section: Introductionmentioning
confidence: 99%